(untitled) (Marketing Journal, 2026)
Abstract This article analysed the theoretical foundations and practical aspects of economic relations among cluster participants. The study examined the impact of cluster systemson production efficiency, resource exchange, innovative cooperation, and competitiveness. The theoretical approaches of Porter, Krugman, and Marshall were systematically reviewed. Using Uzbekistan’s cotton-textile clusters as a case study, the influence of vertical and horizontal integration on production volume, export performance, and employment was evaluated based on statistical data. The analysis demonstrated improved industrial efficiency under cluster-based production organization. The findings confirmed that the development of intra-cluster economic relations strengthened value chains, increased industrial productivity, and expanded export capacity. The results were assessed as an analytical basis for improving economic cooperation among cluster participants. Keywords: cluster, economic relations, competitiveness, vertical integration, horizontal integration, innovation, value chain, textile industry, export.